A phase 2 basket trial of combination therapy with trastuzumab and pertuzumab in patients with solid cancers harboring human epidermal growth factor receptor 2 amplification (JUPITER trial). Issue 32 (7th August 2020) - Takahashi, Kenta; Ishibashi, Eri; Kubo, Toshio; Harada, Yohei; Hayashi, Hideyuki; Kano, Masayuki; Shimizu, Yasushi; Shirota, Hidekazu; Mori, Yukiko; Muto, Manabu; Ishioka, Chikashi; Dosaka-Akita, Hirotoshi; et al.
Abstract: Introduction: Human epidermal growth factor receptor 2 ( HER2 ) gene amplification and mutations have emerged as oncogenic drivers and therapeutic targets not limited to breast and gastric cancers, but also in a variety of cancers. However, even if an actionable gene alteration is found, the incidence of HER2 amplification in these cancers is less than 5%. It is too difficult to conduct a conventional randomized, controlled trial in a rare fraction. Therefore, we have designed a organ-agnostic basket study, which covers a variety of solid cancers harboring HER2 amplification, in 1 study protocol. Methods/Design: This trial is a multicenter, single-arm, basket phase 2 study in Japan. Patients with solid cancers harboring HER2 amplification that have progressed with standard treatment, or rare cancers for which there is no standard treatment, will be eligible. Target cancers include bile duct, urothelial, uterine, ovarian, and other solid cancers where HER2 amplification is detected by comprehensive genomic profiling using next-generation sequencing technology. A total of 38 patients will be treated with combination therapy with trastuzumab and pertuzumab every 3 weeks until disease progression, unmanageable toxicity, death, or patient refusal. The primary endpoint is the objective response rate, and secondary endpoints are progression-free survival, overall survival, and duration of response. Discussion: The aim of this trial is to evaluate the safety and efficacy of combination therapy with trastuzumab and pertuzumab in patients with locally advanced or metastatic, solid cancers harboring HER2 amplification. Instead of focusing on 1 organ type, our trial design uses a basket study focusing on HER2 amplification, regardless of the site or origin of the cancer. The results of our study will advance clinical and scientific knowledge concerning the treatment of locally advanced, rare solid cancers harboring HER2 amplification, using the combination of trastuzumab and pertuzumab. Trial registration: This trial was registered in Japan Registry of Clinical Trials (jCRT) on February 25, 2019, as jRCT2031180150. Abstract : Supplemental Digital Content is available in the text